Latin America: Economic Growth and Productivity Since the 1990s - Aravena-Flores, C; Hofman, A (Taylor and Francis, 2018)
Economic growth since 1990 in Latin America and India has been very different, with low and volatile growth in Latin America and the Caribbean, and sustained high growth in India. The analysis presented in this chapter helps explain the factors behind these different performances, and discusses the challenges Latin America and India face in achieving long-term growth, taking the most immediate determinants into account. A number of exercises, designed to quantify the factors that have driven growth, were therefore carried out on the basis of a “growth accounting” approach. The aim of this analysis is to identify elements that can help gear public policies toward raising growth rates sustainably for the economies of Latin America and the Caribbean. © 2018 selection and editorial matter, Deb Kusum Das; individual chapters, the contributors.